SISTEM SAPAAN KEKERABATAN SESUAI MARGA DALAM MASYARAKAT BAHASA ATOIN METO DI DUSUN OELEKAM DESA OELTUA - Bata, Agnes Novriyanti; Djuli , Labu; Djama , Karolus B. (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The main problem in this study is how to describe the form of kinship greeting system according to clan in Atoin Meto language community in Oelekam Hamlet, Oeltua Village, Taebenu District, Kupang Regency. This study aims to describe the form of kinship greeting system according to clan in Atoin Meto language community in Oelekam Hamlet, Oeltua Village, Taebenu District, Kupang Regency. The method used in this research is descriptive qualitative method. The data collection method used is the listening method with the basic technique of tapping technique. The data in this study are in the form of greeting systems spoken by informants and data sources, namely data obtained from informants totaling 4 people as Atoin Meto people living in Oeltua Village. The results showed that the kinship greeting system in the community in Oelekam Hamlet, Oeltua Village has two forms, namely the kinship greeting system according to the clan and the kinship greeting system in the family. There are seven clan greeting systems and six family greeting systems.